2020
DOI: 10.1108/pijpsm-12-2019-0191
|View full text |Cite
|
Sign up to set email alerts
|

Who is reported missing from Canadian hospitals and mental health units?

Abstract: PurposeInternational literature on missing persons suggests that a significant volume of missing person cases originate from hospitals and mental health units, resulting in considerable costs and resource demands on both police and health sectors (e.g., Bartholomew et al., 2009; Sowerby and Thomas, 2017). In the Canadian context, however, very little is known about patients reported missing from these locations – a knowledge deficit with profound implications in terms of identifying and addressing risk factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Generally, those with a mental disability and/or senility account for more missing person reports than any other documented health characteristic ( n = 406; 44.3%). This could be explained by the growing aging population in Canada, resulting in several adults with cognitive impairments (Ferguson & Huey, 2020), or might represent a high number of people with mental disorders at such settings.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, those with a mental disability and/or senility account for more missing person reports than any other documented health characteristic ( n = 406; 44.3%). This could be explained by the growing aging population in Canada, resulting in several adults with cognitive impairments (Ferguson & Huey, 2020), or might represent a high number of people with mental disorders at such settings.…”
Section: Resultsmentioning
confidence: 99%
“…Focusing on policing implications, research from the UK and Australia highlight that, specific to hospitals and mental health settings, police are implicated in returning over one-third of persons missing from hospitals (Bartholomew et al, 2009; Bowers et al, 1998; Dickens and Campbell, 2001; Meehan et al, 1999; Muir-Cochrane and Mosel, 2008; Wilkie et al, 2014). In Canada, recent research advances that around 12% of all missing person cases reported to the police are initiated by hospitals and mental health units (Ferguson & Huey, 2020). The volume of cases originating from such locations accrues an estimated cost for policing in the UK of around £879,060 per year (Hayden and Shalev-Greene, 2018; Shalev Greene and Pakes, 2013), which is over $1,500,000 CAD.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, even though greater investment in upstream, preventative services would theoretically relieve the police from the responsibility to respond to an array of social problems, it would not completely absolve them of the responsibility. Mental health diagnoses, for example, are a significant predictor for select missing persons cases (Ferguson & Huey, 2020). Given that missing persons are a police responsibility, the police would likely be placed in a position to come into contact with these individuals when found, and it would not be implausible to assume that a small proportion of these contacts may even occur within the context of a mental health crisis.…”
Section: )mentioning
confidence: 99%
“…particular social groups being more at-risk when missing so police frontload resources and resolve cases quicker before they travel far), a number of social and health issues the social groups interact with affecting these incidents (e.g. differences in mental, physical and cognitive capabilities affecting travelling), policing response to each case differing and, ultimately, a slew of other potential reasons (Gibb and Woolnough, 2007;Shalev et al, 2009;Hansen and Dim, 2019;Doyles and Barnes, 2020;Ferguson and Huey, 2020;Ferguson, 2021). This points to the need for additional research unpacking the mechanisms impacting the spatial behaviour patterns of missing people, especially from hospitals.…”
Section: Missing Persons From Hospitalsmentioning
confidence: 99%